2014
DOI: 10.1186/1756-9966-33-2
|View full text |Cite
|
Sign up to set email alerts
|

A novel oncolytic viral therapy and imaging technique for gastric cancer using a genetically engineered vaccinia virus carrying the human sodium iodide symporter

Abstract: BackgroundGastric cancers have poor overall survival despite recent advancements in early detection methods, endoscopic resection techniques, and chemotherapy treatments. Vaccinia viral therapy has had promising therapeutic potential for various cancers and has a great safety profile. We investigated the therapeutic efficacy of a novel genetically-engineered vaccinia virus carrying the human sodium iodide symporter (hNIS) gene, GLV-1 h153, on gastric cancers and its potential utility for imaging with 99mTc per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 24 publications
0
26
0
1
Order By: Relevance
“…Apart from the transforming growth factor-beta-induced protein (TGFBI) which is a secreted ECM component that can play an important role in tumor progression 25 26 , POSTN, parathyroid hormone-like hormone (PTHLH) and secreted phosphoprotein 1 (SPP1) were also predicted to be associated with skeletal system development. Our research group have previously reported that PTHLH can act as a tumor promoter, affecting cell proliferation and the cell cycle in HNC 27 . Thereafter, the expression levels of POSTN and SPP1 were tested in 29 paired HNC samples through real-time PCR.…”
Section: Resultsmentioning
confidence: 97%
“…Apart from the transforming growth factor-beta-induced protein (TGFBI) which is a secreted ECM component that can play an important role in tumor progression 25 26 , POSTN, parathyroid hormone-like hormone (PTHLH) and secreted phosphoprotein 1 (SPP1) were also predicted to be associated with skeletal system development. Our research group have previously reported that PTHLH can act as a tumor promoter, affecting cell proliferation and the cell cycle in HNC 27 . Thereafter, the expression levels of POSTN and SPP1 were tested in 29 paired HNC samples through real-time PCR.…”
Section: Resultsmentioning
confidence: 97%
“…Its oncolytic activity has been documented in several in vitro and in vivo studies. VV carrying the human NIS gene has been investigated as a possible treatment for endometrial cancer (144), pancreatic cancer (145, 146), malignant pleural mesothelioma (147), and gastric cancer (148) by in vitro and in vivo monitoring of infection, distribution, and cytotoxicity. Tumor growth and reduction were measured by 99m TcO 4 − and 124 I − SPECT/CT.…”
Section: Replication-competent Oncolytic Virusesmentioning
confidence: 99%
“…As we have described for infectious diseases, in the development of different vaccines against cancer, various approaches involve the insertion of heterologous genes into common poxvirus strains, such as immunotherapy by the expression of TAA (e.g., MUC1 [578], oncofetal antigen 5T4 [579], PSA [580], CEA [581]), the expression of immunomodulatory genes (e.g., costimulatory molecules-B7.1, B7.2 [582], CD80 [583] or cytokines-IL-2 [584], IFN-β [585], GM-CSF [586]), the expression of suicide genes (e.g., cytosine deaminase [587], purine nucleoside phosphorylase [588]), and the expression of genes used for the imaging as a support for combination therapies (thyroidal sodium iodide symporter NIS [589]).…”
Section: Poxvirus Evolution As Vaccines To Fight Cancermentioning
confidence: 99%